The Authenticity of Jesus’ Crucifixion and Death: A Legal and Theological Review in Response to Polemical Allegation - Christiaan, John Abraham; Dully, Stefanus; Maulany, Rissendo Billyfaughn; Simon, Simon (TELEIOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Abstract: The rise of interpretations from non-Christian religious leaders about Christian teachings is the highlight of the researcher in this study, especially the wrong interpretation of the crucifixion of the Lord Jesus. Non-Christian figures interpret that Jesus was never crucified, but it was someone else who was crucified because Jesus could disappear, besides that the opinions of the interpreters do not agree with each other, some say, Yudah Iscariot, Simon the Cyrenian, Simon the Arab, Barsabas and others. This interpretation contradicts the Christian Faith and the testimony of the Bible, so researchers want to prove with this research to prove that Jesus was really crucified and died on the cross. This research uses descriptive qualitative methods through literature studies supported by historical documents. From the results of the research, it was found that the undeniable fact according to the law that Jesus was crucified on the hill of Golgotha and died, and rose on the third day, as witnessed by eyewitnesses, also reinforced by the testimony of philosophers and early church fathers, as well as testimony from non-Christians that Jesus Christ was really crucified and died on the cross, was buried and rose on the third day.